Brain tumor imaging - Jain, Rajan; Essig, Marco (Thieme, 2016)
Conventional morphologic imaging : MRI remains the workhorse -- Benjamin Cohen, Inna Nutanson, and Girish M. Fatterpekar -- Response assessment in neuro-oncology / Tom Mikkelsen and Tobias Walbert -- Going beyond the conventional morphologic imaging : an overview of functional imaging techniques / Marco Essig and Cem Calli -- Perfusion imaging : DSC MR perfusion / Marco Essig, Joseph Puig Alcantara, and Cem Cali -- Perfusion imaging : dynamic contrast enhanced T1-weighted MRI (DCE-MRI) perfusion / David Fussell and Robert J. Young -- Perfusion imaging : arterial spin labeling / S. Ali Nabavizadeh, Suyash Mohan, Jeffrey M. Pollock -- Perfusion imaging : CT perfusion / Brent Griffith and Rajan Jain -- Diffusion weighted imaging for gliomas / Benjamin M. Ellingson, Bryan Yoo, and Whitney B. Pope -- Diffusion tensor imaging / Bram Stieltjes and Peter Neher -- Functional MRI and diffusion tensor imaging with tractography / Anna Knobel and Robert J. Young -- Metabolic imaging : MR spectroscopy / Isabella Björkman-Burtscher and Pia C. Sundgren -- Molecular imaging : PET and SPECT / Asim K. Bag and Samuel E. Almodóvar -- It's not just the tumor : treatment effects / Brent Griffith and Rajan Jain -- It's not just the tumor : CNS paraneoplastic syndromes and cerebrovascular complications of cancers / Prashant Nagpal and Rajan Jain -- Image guided neurosurgery : intraoperative MRI / Ian Y. Lee -- On the horizon : ultra-high-field MR / Steffen Sammet and Alexander Radbruch -- On the horizon : tumor genomics / Rivka R. Colen, Faisal Tai, and Pascal O. Zinn -- On the horizon : going beyond the conventional MR contrast agents / Josep Puig and Wilson B. Chwang -- On the horizon : molecular imaging / Sanath Kumar, Meser M. Ali, and Ali Syed Arbab
Literaturangaben
Keywords: Aufsatzsammlung; Bildgebendes Verfahren; Hirntumor